The lost honour of the social dimension: Bologna, exports and the idea of the university - Holford, John (Taylor & Francis Online, 2014)
In important respects, European ideas of the university have spread across the world. The principal ‘philosophical’ statements on which this idea of the university is based (Humboldt and Newman) assumed the people inhabiting universities — as students — would come from the youth of a social elite. The outward-facing elements of the Bologna Process, and the European Higher Education Area, aiming mainly at promoting higher education as an export business, focus on students of similar age and social status; its internal mobility dimensions have a similar effect within Europe. The social dimension of Bologna, in contrast, aimed to open higher education more across the social spectrum— though still assuming that the principal groups enrolling would be young. Bologna’s social dimension was strongly influenced by EU debates and policy approaches: while it arguably owed its origins to this fact, the social dimension’s limited success (and more recent displacement from policy, if not rhetoric) can be put down in large part to the difficulties in encapsulating complex and contested social priorities in internationally acceptable indicators, and to the EU’s valorisation of competitiveness in the Lisbon Process (particularly after the onset of recession in 2008).